Study And Design Of A Component-Based Integrated Platform For Web Application - Aslani, Ehsan (2009)
This thesis develops the design of a framework that introduces the basic components and mechanisms of a web application market platform which adds some semantic to the services that this web applications provide and enables trade and composition of services. The framework provides an integrated component based abstract design for the market.